Feature extraction for ferroresonance phenomena in electric power system - (:unkn) unknown (My University, 2009)
In this study, the ferroresonance phenomena are considered under the modeling of the West Anatolian Electric Power Network of 380 kV in Turkey. The ferroresonance event is carried out using the switching to remove the loads at the end of the lines. In this sense, two different cases are taken. At first, the switching is applied at 0.5 second and the ferroresonance effects are observed between 0.5 and 1 second in terms of the voltage variations. As a result the ferroresonance case and steady state case before the ferroresonance are compared with each other using the Fourier transform techniques. Hence, the properties of the ferroresonance event, which are defined between the 125 and 250 Hz, are presented in the frequency domain.
Keywords: Ferroresonance; Power spectral density; Power system modeling; Time-frequency analysis